2018
DOI: 10.1038/s41388-017-0121-z
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolus as an emerging hub in maintenance of genome stability and cancer pathogenesis

Abstract: The nucleolus is the major site for synthesis of ribosomes, complex molecular machines that are responsible for protein synthesis. A wealth of research over the past 20 years has clearly indicated that both quantitative and qualitative alterations in ribosome biogenesis can drive the malignant phenotype via dysregulation of protein synthesis. However, numerous recent proteomic, genomic, and functional studies have implicated the nucleolus in the regulation of processes that are unrelated to ribosome biogenesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
168
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 203 publications
(172 citation statements)
references
References 160 publications
(229 reference statements)
4
168
0
Order By: Relevance
“…The known link between ribosome stress and p53 activity in the light of our new data allows for the exciting hypothesis that AATF mediates its effects on cell death employing this pathway. Based on the interaction between r-proteins and the E3 ubiquitin ligase MDM2, defects in ribosome maturation activate p53 19,36,[51][52][53] . Loss of AATF would thus increase p53 activity linking the roles of AATF in ribosome biogenesis and p53 activity.…”
Section: Discussionmentioning
confidence: 99%
“…The known link between ribosome stress and p53 activity in the light of our new data allows for the exciting hypothesis that AATF mediates its effects on cell death employing this pathway. Based on the interaction between r-proteins and the E3 ubiquitin ligase MDM2, defects in ribosome maturation activate p53 19,36,[51][52][53] . Loss of AATF would thus increase p53 activity linking the roles of AATF in ribosome biogenesis and p53 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Although the nucleolus was observed in cells over 100 years ago, only recently have studies demonstrated its liquid‐like properties such as fusion and flowing . The nucleolus is an MLO, best known as the center of ribosome biogenesis, although it has been associated with numerous other roles including ribonucleoprotein formation, genome stability, and cancer . Nucleoli are spatially associated with nucleolar organizer regions on chromosomal DNA, and show dissociation and regrowth during different stages of the cell cycle.…”
Section: Three Examples: Proteins Mlos and Functionmentioning
confidence: 99%
“…[27] The nucleolus is an MLO, best knowna st he center of ribosome biogenesis, althoughi th as been associated with numerouso ther roles including ribonucleoprotein formation, genome stability,a nd cancer. [28] Nucleoli are spatially associatedw ithn ucleolar organizer regions on chromosomal DNA, and show dissociation and regrowth during different stages of the cell cycle. Internally,n ucleoli are not spatially uniform and instead show more complex sub-structure.…”
Section: Nucleophosmin and The Nucleolusmentioning
confidence: 99%
“…Nucleolar organizer regions (NORs) contain the rRNA genes discussed above are present on five different acrocentric chromosomes are bookmarked during mitosis . This bookmarking provides a basis for the reassembly of these NOR‐bearing chromosomes and biogenesis of nucleoli (Figure ). Interestingly, it was discovered that there is a dominant nucleolus that associates with more of these acrocentric chromosomes.…”
Section: The Challenge Of Cellular Division and Implications For Genomentioning
confidence: 99%
“…Bookmarking of chromatin domains has been proposed to play a significant role in reestablishing fidelity for HCO of the genome . Upon exit from mitosis, the biogenesis of nuclear bodies, which include nucleoli (where ribosomal RNA is transcribed) and histone locus bodies (HLB; where histone mRNA is transcribed), contribute to HCO‐mediated biological control . These physiologically important examples of regulatory compartmentalization are obligatory for the balance between proliferation and cell lineage specificity.…”
Section: Introductionmentioning
confidence: 99%